Comparison of antimicrobial prescribing between two specialist paediatric centres in the UK and Latvia. Issue 3 (21st February 2013) - Sviestina, Inese; Aston, Jeff; Mozgis, Dzintars
Abstract : Objective: To compare the use of antibiotics among hospitalised children in the UK and Latvia at two specialist paediatric centres. Methods: Two point prevalence surveys were undertaken on a single day in May and November 2011. Data collection included demographic details such as gender, age and specialty, prescribed antibiotic(s), indication, dose, frequency, route of administration and day of treatment. The data were analysed using Microsoft Excel and SPSS 20.0. Results: The demographic details at the two institutions were similar. A number of differences were noted in antimicrobial prescribing. The most common groups of prescribed antibiotics were penicillin/β-lactam combinations in the UK and third-generation cephalosporins in Latvia. In both centres the most common therapeutic indication for antibiotic therapy was lower respiratory tract infection, which was predominantly treated in the UK with co-amoxiclav and in Latvia with ampicillin/amoxicillin. The intravenous route was most commonly used in both centres, but this was substantially higher in Latvia than in the UK (mean across both surveys 87.4% vs 62.6%). Conclusions: A number of differences were observed in antibiotic prescribing between these two paediatric centres. By sharing audit data and antimicrobial stewardship initiatives, further changes in practice may be observed at both institutions.